Optimal simple monetary policy rules and welfare in a DSGE model for Hungary - Zoltán M. Jakab; Henrik Kucsera; Katalin Szilágyi; Balász Világi (Magyar Nemzeti Bank, 2010)
We explore the properties of welfare-maximizing monetary policy in a medium-scale DSGE model for Hungary. In order to make our results operational from a policymaker's perspective, we approximate the optimal policy rule with a set of simple rules reacting only to observable variables. Our results suggest that 'science of monetary policy' that is found robust in simple models, holds in this medium-scaled setting as well. That is, the welfare-maximizing policy that aims to eliminate distortions associated with nominal rigidities can be approximated by a simple inflation targeting rule. Adding exchange rate into the feedback rule only marginally improves the stabilization properties of the policy rule. However, a rule reacting to wage inflation can be significantly welfare-improving. These results may suggest that in our medium-sized model the distortions associated with sticky wage setting have at least as important welfare implications as those related to the price stickiness in product markets.
Keywords: E52; E58; E61; 330; monetary policy; central banking; policy design